Hartz IV and the decline of German unemployment: A macroeconomic evaluation - Brigitte Hochmuth; Britta Kohlbrecher; Christian Merkl; Hermann Gartner (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2019)
This paper proposes a new approach to evaluate the macroeconomic effects of the Hartz IV reform in Germany, which reduced the generosity of long-term unemployment benefits. We use a model with different unemployment durations, where the reform initiates both a partial effect and an equilibrium effect. The relative importance of these two effects and the size of the partial effect are estimated based on the IAB Job Vacancy Survey. Our novel methodology provides a solution for the existing disagreement in the macroeconomic literature on the unemployment effects of Hartz IV. We find that Hartz IV was a major driver for the decline of Germany's unemployment and that partial and equilibrium effect where of equal importance. We thereby contribute to the literature on partial and equilibrium effects of unemployment benefit changes. In addition, we are the first to provide direct empirical evidence on labour selection, which can be interpreted as one dimension of recruiting intensity. – – Wir analysieren mit Hilfe eines neuen Ansatzes die gesamtwirtschaftlichen Arbeitsmarkteffekte der Hartz IV Reform. Mit der Reform wurden die Lohnersatzleistungen für viele Langzeitarbeitslose gekürzt. Wir verwenden ein Modell mit unterschiedlichen Arbeitslosigkeitsdauern, in dem die Reform sowohl einen Partial- als auch einen Gleichgewichtseffekt auslöst. Die relative Bedeutung dieser beiden Effekte und die Höhe des Partialeffektes werden mit Hilfe der Stellenerhebung des IABs geschätzt. Unser Ergebnis ist, dass die Hartz IV Reform eine wichtige Ursache für die seit 2005 sinkende Arbeitslosigkeit in Deutschland darstellt, wobei der Partialeffekt und der Gleichgewichtseffekt etwa gleichbedeutend waren. Wir sind die ersten, die zeigen, wie selektiv sich Betriebe bei Neueinstellungen über den Konjunkturverlauf verhalten, was wir als eine Dimension der Rekrutierungsintensität interpretieren.
Keywords: E24; E00; E60; 330; Unemployment benefits reform; search and matching; Hartz reforms